2017
DOI: 10.1007/s12032-017-0959-5
|View full text |Cite
|
Sign up to set email alerts
|

LincRNa-p21: function and mechanism in cancer

Abstract: In view of the rapid development of gene chips and high-throughput sequencing technology, noncoding RNAs (ncRNas) form a high percentage of the mammalian genome. Two major subgroups of ncRNAs that have been identified are the long ncRNAs (lncRNas) and the microRNAs. A number of studies in the past few years have showed crucial functions for lncRNas in cancer. LincRNa-p21 as a p53-dependent transcriptional target gene and a potential diagnostic marker is involved in proliferation, cell cycle, metabolism and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 53 publications
1
64
0
Order By: Relevance
“…However, few studies report the influence of lincRNa-p21 on CRC. In addition, further studies revealed that lincRNA-p21 was associated with malignancy progression, and contributed to the treatment and prognosis of the tumor (18,37,38). The results of the present study indicated that the relative expression of lincRNA-p21 was significantly associated with adjuvant therapy in the CRC tissue.…”
Section: Lncrna-rorsupporting
confidence: 57%
See 2 more Smart Citations
“…However, few studies report the influence of lincRNa-p21 on CRC. In addition, further studies revealed that lincRNA-p21 was associated with malignancy progression, and contributed to the treatment and prognosis of the tumor (18,37,38). The results of the present study indicated that the relative expression of lincRNA-p21 was significantly associated with adjuvant therapy in the CRC tissue.…”
Section: Lncrna-rorsupporting
confidence: 57%
“…ROR expression suppresses p53 to maintain cellular homeostasis (17). Cyclin-dependent kinase inhibitor 1 (CDKN1A), also known as p21, mediates p53-dependent growth arrest (18). LincRNA-p21 is induced by p53 and is expressed ~15 kb upstream of the CDKN1A (p21) on chromosome 17 (15).…”
Section: Association Of Lncrna-p53 Regulatory Network (Lincrna-p21 Lmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the development of high-throughput sequencing and novel computational approaches, lncRNAs have been identified as a significant player in the regulation of gene expression at the post-transcriptional level. Accordingly, there is growing evidence that the lncRNAs served as competing endogenous RNA (ceRNAs) to inhibit the expression or activity of microRNA (miRNA) (11,12). Since miRNA have been largely reported to regulate gene expression, investigating the crosstalk between lncRNAs and miRNA may enable us to better understand the mechanisms underlying the occurrence and development of associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…One of themost famous cis-acting element is lncRNAs X-inactivation-specifictranscript (Xist), which recruits polycomb repressive complex 2 (PRC2) leading to H3 acetylation and methylation, further inducing silence of whole X-chromosome [19, 20]. Recent study showed that long intergenic noncoding RNA p21 (lincRNA-p21) mediated p53 downstream gene [21]. The regulation of lincRNA-p21 belonged to hnRNP-K protein dependent transcriptional silencing and play a negative role in hindering expression of p53 downstream gene [22].…”
Section: Regulation Effect Of Lncrnasmentioning
confidence: 99%